2019
DOI: 10.1109/tro.2019.2931483
|View full text |Cite
|
Sign up to set email alerts
|

Rest-to-Rest Trajectory Planning for Underactuated Cable-Driven Parallel Robots

Abstract: This paper studies the trajectory planning for underactuated cable-driven parallel robots (CDPRs) in the case of rest-to-rest motions, when the motion time and the path geometry are prescribed. For underactuated manipulators, it is possible to prescribe a control law only for a subset of the generalized coordinates of the system. However, if an arbitrary motion is prescribed for a suitable subset of these coordinates, the constraint deficiency on the end-effector motions leads to the impossibility of bringing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…These assumptions neglect not only all effects caused by the elastic nature of cables, which may be negligible in some small-to-medium-scale applications, but also the kinematics of the guidance system. Geometrical-model errors can be limited by accounting for the pulley geometry [4,32], but the model and control complexity is usually increased. As an alternative, if the standard kinematic model is to be used without inherent geometrical errors, special design techniques of the actuation units and guidance systems can be used, as discussed in the following.…”
Section: Design Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…These assumptions neglect not only all effects caused by the elastic nature of cables, which may be negligible in some small-to-medium-scale applications, but also the kinematics of the guidance system. Geometrical-model errors can be limited by accounting for the pulley geometry [4,32], but the model and control complexity is usually increased. As an alternative, if the standard kinematic model is to be used without inherent geometrical errors, special design techniques of the actuation units and guidance systems can be used, as discussed in the following.…”
Section: Design Strategiesmentioning
confidence: 99%
“…In general, the presence of pulleys in the guidance system makes the system reliable, but complicates the geometrical model of the robot. This issue can be faced in two ways: by adopting a more complex model, which includes pulley kinematics for CDPR control [4,32,43], or by ignoring the actual geometry of the system, and accepting several modeling errors. Otherwise, particular layout and orientations of the pulley system must be adopted.…”
Section: Guidance Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…25 For underactuated manipulators, it is possible to prescribe a control law only for a subset of the generalized coordinates of the system. Hereafter, the article studies the trajectory planning for underactuated CDPRs in the case of rest-to-rest motions, when both motion time and path geometry are prescribed in the study by Ida`et al 26 Unfortunately, the control algorithm demonstrated in those studies are complex and their implementation is laborious, so employing them in real-time control is tough. Furthermore, the aforementioned findings focus on controlling the suspended platform and none proposes the control schemes to grasp objects with different shapes and colors.…”
Section: Introductionmentioning
confidence: 99%